Cooperative Approaches and Academic Motivation towards Enhancing Pre-Service Teachers' Achievement - Dolors Cañabate; Maria Eugènia Gras; Teresa Serra; Jordi Colomer (MDPI AG, 2021)
This paper describes a quantitative study that explores both the degree of preservice teachers' (PSTs) motivation and achievement, and the dimensions of need-supportive teaching, when PSTs were involved in designing and implementing contextualized physical cooperative challenges (CPCCs) in primary schools. The analysis was based on the PSTs' perceptions of the dimensions of need-supportive teaching (namely autonomy support, structure, and involvement), and the dimensions of motivation. Need-supportive teaching was evaluated through a version of the Teacher as a Social Context Questionnaire (TASC-Q), and motivation through a SMOTIV motivation questionnaire. Results showed that the dimensions of the teaching process were all positively correlated, thus, implying the importance of a teacher's role in supporting autonomy, providing structure, and being involved. While motivation during the in-class definition of the CPCCs was correlated with the teachers' involvement, the out-of-class implementation of the CPCCs was found to correlate with the three dimensions of teaching, thus, implying that the PST students' perceptions of developing instructional approaches in schools is mediated by the role their university teachers play in defining and structuring all aspects of the teaching process. Students' achievement, on the other hand, was a process that relied on the synergies between the teachers' involvement and the PST student motivation during the stage when the CPCCs in the classroom environment were defined. This interlink responds to the constructivist position adopted to implement a cooperative approach in the university that, in turn, responds to assessing a student-centered cooperative-based learning approach.